(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
The lack of knowledge of pregnant women about preparation for childbirth is one of the causes of mothers experiencing anxiety when facing childbirth. This study aims to study the relationship between maternal knowledge of pregnant trimester III with anxiety level in dealing with childbirth in the Puskesmas Pasar Ikan. Type of research is analytic observational with cross sectional design. The population in this study were all third trimester pregnant women in the working area of Pasar Ikan Puskesmas. The number of samples was 31 trimester III pregnant women. The sample collection technique used was purposive sampling. Data collection techniques using primary data. The data analysis technique used the Chi-Square test (c2). To determine the closeness of the relationship, the Contingency Coefficient (C) test is used. The results showed that 31 trimester III pregnant women were 29 mothers (93.5%) who had good knowledge, 16 people (51.6%) had mild anxiety levels and there was no relationship between knowledge of third trimester pregnant women and anxiety levels in facing childbirth. It is hoped that the Puskesmas can make policies in an effort to improve the quality of health services regarding preparation for childbirth through counseling or health education.